The Causal Relationship between Mathematical Creativity, Mathematical Aptitude and Mathematical Problem-Solving Performance A Cross-Lagged Panel Analysis - Tyagi, Tarun Kumar (INDIAN EDUCATIONAL REVIEW, 2016)
The Cross-lagged Panel Analysis (CLPA) was used to investigate the causal relationship between mathematical creativity, mathematical aptitude and mathematical problem-solving performance. 480 students studying in Class VIII were selected through a random cluster technique from nine Intermediate and High Schools of Varanasi District, India. Mathematical creativity, mathematical aptitude and mathematical problem-solving performance tests were administered three times, at intervals of four months. The CLPA uncovered a significant relationship and revealed that mathematical creativity was found to be causally predominant over mathematical aptitude (i.e., higher mathematical creativity leads to higher mathematical aptitude). Furthermore, mathematical problem-solving performance was found to be the cause of mathematical aptitude and mathematical creativity both (i.e., higher mathematical problem-solving performance leads to higher mathematical aptitude and mathematical creativity).